Low‐fluenced erbium:yttrium‐aluminium‐garnet laser treatment in combination with broadband light pretreatment for various pigmentation disorders in Asian patients. (1st March 2019) - Kim, Heesu; Park, Jiho; Zheng, Zhenlong; Cho, Sung Bin
Summary: Background: Low‐fluenced 2940‐nm erbium (Er):yttrium‐aluminium‐garnet (YAG) resurfacing elicits ablative photothermal tissue reactions confined to the uppermost parts of the epidermis. Objective: To demonstrate the efficacy and safety of low‐fluenced ablative Er:YAG laser treatment in combination with broadband light (BBL) pretreatment for various pigmentation disorders. Methods: In total, 35 Korean patients with various pigmentation disorders were pretreated with BBL, and then, low‐fluenced Er:YAG laser resurfacing was performed with a beam size of 4 mm and a fluence of 1.0‐1.5 J/cm 2 . Results: An average of 1.1 ± 0.4 sessions of combined BBL and low‐fluenced Er:YAG resurfacing treatment was delivered to the patients. Most post‐Er:YAG scaling fell off spontaneously over 3‐5 days, and most of the post‐BBL crusting disappeared spontaneously over 5‐7 days. At 2 months after final treatment, the mean global aesthetic improvement scale score for the clinical improvement of pigmentation lesions was estimated as 2.5 ± 0.8, and that for the improvement of overall skin tone, texture, and wrinkles was 2.8 ± 1.0. Conclusion: Our data demonstrated that post‐BBL, low‐fluenced Er:YAG laser resurfacing can be used to effectively treat various pigmentation disorders in Asian patients. Further improvements in overall skin tone, texture, and wrinkles were also achieved without major side effects.